Contos Novos com novos fios: Mário de Andrade e a modernidade narrativa - Rios, Rita de Cássia Oliveira (2008)
This dissertation presents two aims accomplished in three moments: 1. study of the form of the short story genre. 2. analysis of the intradiegetico narrator and his manners of telling. 3. synthesis of the three ways of narrating e their processes. The purpose of the investigation is the modernist short story of Mário de Andrade treated by diacronyc, according to researchers, such as Julio Cortázar, Afrânio Coutinho, Anatol Rosenfeld, Walter Benjamin, Ricardo Piglia, André Jolles, and Mário de Andrade himself, that assume the function of writer, poet, critic and intellectual of Brazilian Modernism. The concept applied to the reading practice of the corpus of Contos Novos becomes an answer to the intersection of two stories that are present in the universe of the narration, that forms the innovatory profile of the short story and of the teller of twentieth century. The intention of the reading of the three short stories Vestida de preto, O Peru de Natal e Tempo da camisolinha is to recognize the connections of the elements that differentiate in the short stories, resulting in an oblique and intersectional reading, that, in the last phase, reveals the narrative modernity, indicating a critical message of Mário de Andrade to the modern reader of twenty century. The first chapter, with the title Between the traditional short story and the modern, modernist and Brazilian short story: differences of the act of narrating , presents the correlations between the traditional short story and the components of the modern and Brazilian short story: narrator, plot, character, temporalty, linear aspect, succession, time, and space. The second chapter, Telling stories, causos and biographies , focuses the telling, presenting the portrait of Juca character associated to other circumstances, to other techniques, having the function of narrator-character in the three stories. The chapter three indicates the connections between the processes of the act of narrating that reveal the plays of time and space, processes and connections between them, emphasizing the implicit theses in Contos Novos and the cause of original denomination. In last considerations, the research results show to a synthesis of functional elements and structural of the innovatory short stories of Mário de Andrade. We consider that these characteristics have importance, not only in the initial project of this dissertation, but also in the critical interpretation occurred afterwards